Medieval nanotechnology: Thickness determination of Zwischgold samples - Wu, Qing; Watts, Benjamin; Döbeli, Max; Müller, Julian; Butz, Benjamin; Lombardo, Tiziana; Schmidt-Ott, Katharina; Fink, Rainer; Nolting, Frithjof; Ganz, David (Journal of Cultural Heritage, 2021)
A special gilding material called Zwischgold has been frequently observed in medieval gilded artefacts. As a bilayer metal leaf made from gold and silver, it exhibits similar but slightly paler golden colour tone compared to pure gold. Zwischgold surface can be darkened quickly due to the corrosion of its silver base. Despite its frequent mentions in medieval guild statutes, the production of Zwischgold and its important technological parameters have been under a veil of secrecy since the Middle Ages. Here, we examine the thicknesses and materials proportions of medieval Zwischgold, through high-resolution scanning electron microscopy coupled with energy dispersive X-ray analysis (SEM-EDX) on a large number of samples taken from late medieval gilded sculptures. We observe that medieval Zwischgold contains ultra-thin gold layers in a thickness range of ca. 20–50 nm, indicating the employment of high-precision technologies in manufacturing of delicate art materials in the late medieval period. It further clarifies some ambiguity in gilding history, regarding the colour appearance of medieval Zwischgold. As supportive data, Rutherford backscattering spectrometry (RBS) and scanning transmission electron microscopy (STEM) were applied, in order to confirm the precision and accuracy of the sample preparation and the SEM analysis.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Gilding; Medieval; Nanoscale; SEM; Thickness; Zwischgold